LAYANAN BIMBINGAN KARIR DALAM UPAYA MENGURANGI KECEMASAN SISWA SMA DALAM PEMILIHAN KARIR - Asyavira Mahardini Putrie; Nurus Saadah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research aims to determine the results of services in an effort to reduce students' anxiety in choosing a career using the SLR (Systrmatic literature review) method. Literature sources were obtained from the crossref metadata database in the Indonesian Bebrahasa journal for 2016-2023. In this research there are several results from career guidance services in an effort to reduce students' anxiety in choosing a career, including; (1) career guidance services; (2) career anxiety; and (3) the role of guidance and counseling teachers. There are several strategies from guidance services that have provided positive results in the success of career guidance services, including; (1) career guidance services, (2) trait factors, (3) Rational Emotive Therapy (TRE), (4) cognitive information processing career counseling, and (5) Client Centered Therapy.